1998
DOI: 10.1002/hep.510270336
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of hepatitis A vaccine in patients with chronic liver disease

Abstract: Acute hepatitis A superimposed on chronic liver disease (CLD) has been associated with severe or fulminant hepatitis. An open, multicenter study was performed to compare the safety and immunogenicity of an inactivated hepatitis A vaccine in patients with CLD with that in healthy subjects. A secondary objective was to compare the safety of the hepatitis A vaccine with that of a commercial hepatitis B vaccine in subjects with chronic hepatitis C. A total of 475 subjects over the age of 18 years were enrolled int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
128
1
13

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(149 citation statements)
references
References 26 publications
7
128
1
13
Order By: Relevance
“…Although the HAV vaccine is effective in patients with chronic liver disease, the geometric mean titer of HAV antibody induced by the vaccine in these patients is lower than in those without chronic liver disease, and, therefore, high rates of protection against HAV are only achieved after the administration of both doses of the vaccine. 41,42,47 Although some of our patients who received only one dose of the vaccine completed the full course after our study ended, it does raise some concerns that these individuals may not be adequately protected against HAV infection. Additional studies are needed to determine whether an accelerated vaccination schedule 48 or the use of the combination HAV and hepatitis B virus vaccine 49 improves physician and patient compliance with vaccination.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the HAV vaccine is effective in patients with chronic liver disease, the geometric mean titer of HAV antibody induced by the vaccine in these patients is lower than in those without chronic liver disease, and, therefore, high rates of protection against HAV are only achieved after the administration of both doses of the vaccine. 41,42,47 Although some of our patients who received only one dose of the vaccine completed the full course after our study ended, it does raise some concerns that these individuals may not be adequately protected against HAV infection. Additional studies are needed to determine whether an accelerated vaccination schedule 48 or the use of the combination HAV and hepatitis B virus vaccine 49 improves physician and patient compliance with vaccination.…”
Section: Discussionmentioning
confidence: 96%
“…However, several studies have shown that vaccination against HAV is safe and effective in patients with chronic liver disease, especially in those with well-compensated liver disease. 41,42 In addition, HAV vaccination has been shown to be cost-effective in patients with chronic liver disease. 43,44 Although the HAV vaccine is also safe in patients with decompensated disease and in liver transplant recipients, the immunogenicity of the vaccine is substantially lower than in those with compensated liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…In December 1996, the Advisory Committee on Immunisation Practices from the Centres for Disease Control and Prevention in Atlanta (USA) recommended active immunization against HAV infection of all patients with chronic liver disease [18], since the new HAV vaccine was shown to be safe and immunologically active, even though the amounts of anti-HAV in patients with liver disease after vaccination are lower than those in healthy subjects [21,22]. An Italian Consensus Conference held in Rome in 1995 [23] concluded that the lack of epidemiological data on this topic in Italy and the lack of information on the incidence of acute HAV infection in subjects with liver disease did not allow a conclusive statement to be made regarding the immunization strategy to be adopted for patients with chronic hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the frequency of adverse effects, except fever, diminished with successive doses. 13,17 Immune response to infection by HAV is complex, but clearly involves cellular and humoral immunity, cellular Van Herck et al 18 developed mathematical models to assess the development of anti-HAV antibodies, after administration of 2 inactivated vaccines (Havrix and Avaxim). The two vaccines showed similar results; when the antibody levels were higher than 20 mUI/mL, they remained for at least 10 years after completing the vaccination scheme.…”
Section: Hepatitis a Vaccinementioning
confidence: 99%
“…The response of patients with decompensated chronic hepatic disease is known to be lower, with lower antibody levels and lower seroconversion rates, when compared to those with compensated disease. 6,17,33,34 Response to the vaccine was recently assessed in Porto Alegre, in children with Down syndrome and chronic hepatopathies. [35][36][37] Satisfactory seroconversion results were obtained, but with lower antibody titres than those in normal children in the same age group.…”
Section: Hepatitis a Vaccinementioning
confidence: 99%